Comparative calculation of heat exchange with the ground in residential building including periodes of heat waves = Weryfikacja niestacjonarnego modelu do obliczeń temperatury w jednorodzinnych budynkach mieszkalnych podczas fal upałów - Staszczuk, Anna; Kuczyński, Tadeusz; Wojciech, Magdalena; Ziembicki, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper provides verification of 3D transient ground-coupled model to calculation of heat exchange between ground and typical one-storey, passive residential building. The model was performed with computer software WUFI?plus and carried out to estimate the indoor air temperatures during extending hot weather periods.
Keywords: niestacjonarna wymiana; model do obliczeń; wymiana ciepła z gruntem; fale upałów; szeregi czasowe; transient calculation model; ground heat storage; heat waves; time series